Morphological and thermal analyses of flexible polyurethane foams containing commercial calcium carbonate - Sant'Anna, Sabrina Sá; de Souza, Denilson Arlindo; Carvalho, Cornélio de Freitas; Yoshida, Maria Irene (Eclética Química, 2008)
One filler often utilized in flexible polyurethane foams is calcium carbonate (CaCO3) because it is non-abrasiveness, non-toxicity and facilitated pigmentation. However, it is observed that the excess of commercial CaCO3 utilized in industry possibly causing permanent deformations and damaging the quality of the final product. The effect of different concentrations of commercial CaCO3, in flexible foams, was studied. Different concentrations of CaCO3 were used for the synthesis of flexible polyurethane foams, which were submitted to morphological and thermal analyses to verify the alterations provoked by the progressive introduction of this filler.